OP0202 Long-Lived CD19-Negative Human Plasma Cells Are Generated at The Plasmablast To Plasma Cell Transition. (15th July 2016) - Arumugakani, G.; Stephenson, S.; Doody, G.; Rawstron, A.C.; Emery, P.; McGonagle, D.; Tooze, R.
Abstract : Background: B-cells are key mediators in a wide variety of autoimmune disorders as evidenced by the clinical response to B-cell depletion. Lack of response in a proportion of patients could be due to long-lived plasma cells (PCs) that are resistant to B-cell depletion therapy. Thus long-lived PCs in addition to their central role in humoral immunity are also involved in autoimmunity. Absence of CD19 expression, a feature of neoplastic PCs, identifies a minor subpopulation of normal human bone marrow PCs potentially linked to long-lived cells [1]. Whether CD19 neg PCs are "aged" cells that have gradually lost CD19 expression, or derive from a distinct differentiation decision is not established. Objectives: We sought to ascertain whether human CD19 neg PCs are derived at the plasmablast to PC transition or are established by gradual loss of CD19 expression with increasing PC age. Methods: We performed a sensitive flow cytometric analysis of CD19 expression during the human acute immune responses to flu vaccination, and tracked the generation and maintenance of CD19-negative PCs using CD40:CD40L and TLR mediated in vitro human PC differentiation systems [2]. Results: Using intracellular staining for IRF4 alongside conventional surface markers such as CD27, CD38, CD95 and CD20, we robustly identify a CD19 neg plasmablast population present in steady state peripheral blood. The CD19 neg plasmablasts expanded during the acute plasmablast response to flu vaccination (p=0.063) but the degree of expansion was smaller compared to CD19 pos plasmablasts. Influenza specific CD19 neg plasmablasts were detectable 6 days after vaccination in the peripheral blood by ELISpot. CD19 neg state was established at the plasmablast to PC transition in both CD40:CD40L and TLR mediated B-cell differentiation in vitro. CD19 neg PCs increase as a percentage of surviving PCs with time in vitro at all the three subsequent time points compared to the previous time point (p=0.0009, 0.0015 and 0.0179). Flow-cytometrically sorted CD19 neg PCs can be maintained independent of CD19 pos PCs. Conclusions: CD19 neg PCs are independently established as an early event during human PC differentiation and predominantly do not derive by age-associated conversion from CD19 pos PCs. Absence of CD19 expression does not provide evidence of PC age, but may identify PCs with greater potential for longevity in humans. Understanding the plasmablast to PC transition is vital in determining strategies for depletion of long-lived PCs and stages of immune response at which they can be employed for treatment of autoimmune disorders. References: Mei HE, et al. Blood 2015, 125(11):1739–1748. Cocco M, et al. Journal of Immunology 2012, 189(12):5773–5785. Disclosure of Interest: None declared